The Benefits of Variable Speed Operation in Hydropower Plants Driven by Francis Turbines - Edson Bortoni; Zulcy de Souza; Augusto Viana; Helcio Villa-Nova; Ângelo Rezek; Luciano Pinto; Roberto Siniscalchi; Rafael Bragança; José Bernardes (Energies, 2019)
Climate change and environmental degradation has resulted in a reduction in water inflow at hydropower plants, as well as a decrease in reservoir levels. Existing hydropower plants suffer from water head reduction, mainly with decrease in efficiency of energy conversion in hydro turbines. This paper showcases the benefits of operations with variable speed in existing hydropower plants, when working at a lower water head than the rated one. Theoretical analyses and tests were performed in a special constructed laboratorial setup aiming at evaluating the amount of efficiency recovery with variable speed operation. Connection alternatives for a constant frequency grid and applications of the learned concepts in an existent hydropower plant are presented. The investigations were applied to the Furnas hydropower plant. The results point out that economic feasibility of the application can be achieved.